Qur'an And Al-Hadits Model-Based Education In Increasing Islamic Civilization - Zakariya, Din Muhammad (Prodi Pendidikan Agama Islam - Fakultas Agama Islam ( FAI ), 2019)
AbstractThis study aimed to explore how educational models that can realize highemergenceofIslamic civilization; how civilization produced by education basedon the revelation of the Qur'an and Al-Hadits); and what happens when acivilization based education override revelation (Al-Quran and Al-Hadits). Thisstudy is intended as an exploration efforts and the transformation of science intothe Islamic education system is an integral and operationally. This type ofresearch is the approach of the literature; the data collection method: the methodof documentation and observation method, while the method of the interview as amethod of investigation to collect data related to this study. Analysis of the dataused in this study is a non-statistical analysis. The research result is concluded:first,the emergence of education that can realize the high Islamic civilization iseducation based on revelation; second,civilization produced by education basedon revelation (Al-Quran and Al-Hadits) is a civilization which brings benefit inthis world and happiness in the hereafter. Third,when civilization based educationoverride revelation (Al-Quran and Al-Hadits) then there is the deterioration anddestruction. Keywords: education, civilization of Islam, the Qur'an and al-Hadits